The Effect of Experiential Learning Models Toward Writing Skills of Narration Primary School Student - Risma Nuriyanti; Rahman Rahman; Ernawulan Syaodih; Prana Dwija Iswara; Agus Muharam (Universitas Sebelas Maret, 2019)
Learning to write in elementary school is currently not getting serious attention. This results in the poor quality of students' narrative writing. This study aims to determine the effect of experiential learning models on the narrative writing skills of elementary school students. The method used is a quasi-experimental research design with a nonequivalent control group design. The population in this study was the fourth-grade students at the UPI Lab school Elementary School, amounting to 47 students and divided into two classes, namely the experimental class and the control class. The results showed that there were significant differences between the experimental class posttest and the control class. From these results, it can be concluded that the experiential learning model significantly influences the narrative writing skills of elementary school students. Thus students get meaningful learning and teachers get alternative learning to write for students to create meaningful learning with analytical assessment in the form of content, content, information, grammar, and mechanical organization.